Water-Based Barrier Adhesives

By using water-based barrier adhesives, including polyurethane and water-soluble polymers, to form food packaging films with improved oxygen and water vapor barrier properties, the problems of high transmittance and insufficient adhesion strength in the prior art are solved, and the problem of high transmittance and insufficient adhesion strength is achieved. Efficient food packaging film design.

CN114302937BInactive Publication Date: 2025-01-10THAI POLYETHYLENE CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202080059780.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-03
Filing Date
2020-09-03
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The barrier films in the prior art have problems such as excessive oxygen transmittance and water vapor transmittance, insufficient long-term adhesion strength and poor recycling ability in food packaging applications.

Method used

A water-based barrier adhesive is employed, which consists of polyurethane, water-soluble polymer (containing hydroxyl groups) and water, and may contain additives such as defoaming agents and surfactants, to form a barrier film, preferably a layer Film compression structure.

Benefits of technology

It significantly improves the oxygen transmittance and water vapor transmittance of the barrier film, combines good film appearance and adhesion characteristics, and improves the recycling capacity, so that the laminated film can reach more than 95% of the single-material recyclable group point.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003516460810000121
    Figure BDA0003516460810000121
  • Figure BDA0003516460810000131
    Figure BDA0003516460810000131
Patent Text Reader

Abstract

The present invention relates to a water-based barrier adhesive comprising: a polyurethane; at least one water-soluble polymer, wherein the water-soluble polymer comprises at least one hydroxyl group; and water; a barrier film comprising the water-based barrier adhesive; a method for preparing the water-based barrier adhesive; and use thereof in food packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a water-based barrier adhesive; a method for preparing the same; and uses thereof. Background Art

[0002] Barrier films are important in food packaging applications to preserve and extend the shelf life of food. Individual barrier films can be single-layer or multi-layer. The performance of the barrier depends largely on the oxygen transmission rate and water vapor transmission rate. The film material and structural design depend on the barrier properties required for the specific application and product type.

[0003] WO 2019 / 060026 A1 discloses a laminated film structure including an adhesive layer having gas and moisture barrier properties. The disclosed laminated film structure includes films bonded together with an adhesive composition having barrier properties, such as controlling oxygen and / or water vapor transmission rates. However, the oxygen transmission rates of these laminated films are too high for various applications.

[0004] US 2016 / 0040035 A1 discloses an aqueous coating agent, which comprises (A) an aqueous polyurethane resin comprising a polyurethane resin having an acid group and a polyamine compound, (B) a water-soluble polymer, and (C) an inorganic layered mineral as main components, wherein the solid formulation ratio occupied by the aqueous polyurethane resin (A), the water-soluble polymer (B) and the inorganic layered mineral (C) in the total solid content of the aqueous coating agent is within the approximate range shown below. Aqueous polyurethane resin (A): 5 to 60 mass%, water-soluble resin (B): 25 to 80 mass%, inorganic layered compound (C): 8 to 20 mass%. However, these materials show an oxygen permeability that is too high for various applications.

[0005] However, the materials known in the prior art suffer from insufficient barrier properties, long-term adhesion strength (adhesion stability), product shelf life and recyclability.

[0006] Therefore, there remains a need for barrier films and compositions for preparing the same having improved properties, particularly for use in food packaging applications.

[0007] It was therefore an object of the present invention to provide a barrier film which overcomes the disadvantages of the prior art, in particular with regard to its oxygen and water vapour permeability. Summary of the invention

[0008] This object is achieved by a water-based barrier adhesive comprising: a polyurethane; at least one water-soluble polymer, wherein the water-soluble polymer comprises at least one hydroxyl group; and water.

[0009] A "water-based barrier adhesive" coating composition may be referred to herein as a coating composition used to coat a substrate to provide adhesion and / or barrier properties. The coating composition (water-based barrier adhesive) may include a polyurethane and one or more water-soluble polymers.

[0010] As used herein, the term "barrier adhesive" shall generally encompass any barrier coating and is not limited to adhesives only.

[0011] The present invention provides a coating composition (water-based barrier adhesive) that can be used as an adhesive and / or as a barrier. The coating composition is an aqueous composition. That is, it can be applied to a substrate in the form of an aqueous solution and then dried to form a layer that adheres to the surface of the substrate and simultaneously acts as a barrier. The layer may contain water or a large amount of water.

[0012] The coating composition can be used to form a barrier film, preferably a laminate film.The coating composition can be applied to a substrate and then optionally covered with a laminate layer to form a laminate film, such that the coating composition is disposed between the substrate and the laminate layer.

[0013] The water-based barrier adhesive comprises a polyurethane; one or more water-soluble polymers, wherein the one or more water-soluble polymers comprise -OH (hydroxyl) groups; and water.

[0014] The composition may further comprise one or more optional additives, preferably selected from a group consisting of a defoaming agent, a dispersant, a tackifier, a surfactant, a plasticizer, a wetting agent, a thickener, a biocide, an antioxidant, a crosslinking agent, a hardener, and an adhesion promoter, or a mixture thereof. The composition may comprise at least one additive in an amount of 0.1 to 10 wt % relative to the total weight of the water-based barrier adhesive.

[0015] The water-based barrier adhesive may comprise polyurethane in an amount of 1 to 30 wt%, preferably 1 to 20 wt%, more preferably 1 to 10 wt%, even more preferably 2 to 8 wt%, most preferably 3 to 6 wt%, relative to the total weight of the water-based barrier adhesive.

[0016] The water-based barrier adhesive may contain 5 to 60 wt%, preferably 5 to 40 wt%, preferably 5 to 30 wt%, preferably 5 to 20 wt%, preferably 5 to 15 wt%, preferably 7 to 12 wt% of at least one water-soluble polymer, relative to the total weight of the water-based barrier adhesive.

[0017] The water-based barrier adhesive may contain water in an amount of 40 to 94 wt%, preferably 50 to 94 wt%, preferably 70 to 94 wt%, preferably 80 to 95 wt%, preferably 85 to 95 wt%, preferably 80 to 90 wt%, relative to the total weight of the water-based barrier adhesive.

[0018] The water-based barrier adhesive may consist of polyurethane, at least one water-soluble polymer and water. The amounts of all components of the water-based barrier adhesive total 100 wt%. Throughout the disclosure, "comprising" may preferably be "consisting of".

[0019] The polyurethane and the at least one water-soluble polymer may be included in the water-based barrier adhesive in a weight ratio of 5:1 to 1:30, preferably 2:1 to 1:20, preferably 1:1 to 1:10, preferably 1:1 to 1:5, preferably 1:1 to 1:3.

[0020] The polyurethane may be a solid containing 5 to 50 wt% of water relative to the total weight of the polyurethane. The polyurethane may be a polyurethane that is a dispersion in water (aqueous dispersion; polyurethane dispersion). Preferably, the polyurethane dispersion has a solid content of 20 to 50 wt%, preferably 25 to 40 wt%, preferably 30 to 35 wt%, relative to the total weight of the dispersion. In other words, the polyurethane may be present as a solid in water in an amount of 20 to 50 wt%, preferably 25 to 40 wt%, and preferably 30 to 35 wt%, relative to the total weight of the solid.

[0021] The polyurethane may be an aliphatic polyurethane, preferably obtained from (A) polyether polyols, polyester polyols and combinations thereof; and (B) an aliphatic diisocyanate, preferably hexamethylene diisocyanate (HDI), pentamethylene diisocyanate (PDI), isophorone diisocyanate (IPDI), methylene bis(4-cyclohexyl isocyanate) (HMDI), 2,2,4-trimethylhexamethylene diisocyanate (TMDI) and combinations thereof.

[0022] The polyurethane may contain aliphatic polyether urethane and / or aliphatic polyester urethane. Preferably, the polyurethane contains polyether urethane as a major component and aliphatic polyester urethane as a minor component. The ratio of aliphatic polyether urethane to aliphatic polyester urethane may be in the range of 1:1 to 5:1, preferably 1.2:1 to 3:1, more preferably 1.5:1 to 2:1.

[0023] The aliphatic polyurethane preferably has a number average molecular weight (Mn) of about 30,000 to 80,000 g / mol, and / or a weight average molecular weight (Mw) of about 40,000 to 90,000 g / mol, and / or a Z average molecular weight (Mz) of about 45,000 to 95,000 g / mol. The polyurethane preferably has a polydispersity index in the range of about 1 to 3, preferably 1 to 2, more preferably 1 to 1.25.

[0024] The polyurethane dispersion may have a solution viscosity in the range of 1 to 300 mPas, preferably 20 to 500 mPas, preferably 30 to 500 mPas, preferably 30 to 200 mPas, more preferably 50 to 200 mPas.

[0025] The average particle size (=particle diameter of the polyurethane particles in the aqueous dispersion) is in the range from 10 nm to 500 nm, preferably from 20 to 250 nm, preferably from 50 to 200 nm, preferably from 100 nm to 200 nm.

[0026] The water soluble polymer may be selected from the group consisting of polyvinyl alcohol, poly(ethylene vinyl alcohol), polyvinyl acetate, poly(ethylene vinyl acetate), cellulose acetate, and mixtures thereof.

[0027] The water-soluble polymer may have a degree of hydrolysis of 70 to 100% relative to the total number of hydrolyzable groups in the water-soluble polymer.

[0028] The water-soluble polymer may have a weight average molecular weight of 500 to 50,000 g / mol, preferably 20,000 to 40,000 g / mol.

[0029] The water-based barrier adhesive may further comprise a water-soluble solvent. Relative to the total weight of the water-based barrier adhesive, the water-based barrier adhesive may comprise 0.1 to 50 wt%, preferably 0.1 to 30 wt%, more preferably 10 to 20 wt% of a water-soluble solvent. The water-soluble solvent may be selected from the group consisting of methanol, ethanol, propanol, butanol, and mixtures thereof.

[0030] The object is also achieved by a barrier film comprising a substrate and a barrier adhesive layer coated at least on the surface of the substrate, wherein the barrier adhesive comprises a water-based barrier adhesive as defined herein. According to one embodiment, a barrier film is provided, comprising a substrate and a barrier adhesive layer coated at least on the surface of the substrate, wherein the barrier adhesive consists of a water-based barrier adhesive as defined herein. According to one embodiment, a barrier film is provided, comprising a substrate and a barrier adhesive layer coated at least on the surface of the substrate, wherein the barrier adhesive layer is obtainable by coating a water-based barrier adhesive on a substrate. The water-based barrier adhesive is coated on the surface of the substrate to form a barrier layer adhered to the surface. The barrier adhesive layer can be obtained by coating a water-based barrier adhesive on the surface of the substrate (respectively, the coating layer obtained in the aforementioned coating) once or multiple times.

[0031] The barrier adhesive layer coated on the substrate has a thickness of 0.1 to 10 μm (eg, 1 to 10 μm, 1 to 5 μm, 1 to 2 μm).

[0032] Water-based barrier adhesives can be used at 0.1 to 5 g / m2 , preferably 1 to 3 g / m 2 , more preferably 1.5 to 2.5 g / m 2 amount applied on the surface.

[0033] The barrier film may further include a laminate layer adjacent to the barrier adhesive layer, wherein the barrier adhesive layer is disposed between the laminate layer and the substrate.

[0034] The substrate can be a polymer, such as a polyolefin, PET, nylon or paper-based substrate. Preferably, the substrate is a polyolefin, such as a polyethylene and polypropylene-based substrate. The substrate can be a longitudinally oriented or biaxially oriented polyolefin. The substrate can be coated with a metal oxide layer, such as aluminum oxide or silicon oxide. The substrate can be treated with a corona to enhance the hydrophilicity of the substrate before applying the barrier adhesive or coating. The substrate can include polyethylene, polypropylene or paper, preferably consisting of polyethylene, polypropylene or paper.

[0035] The laminating layer may comprise, preferably consists of, polyethylene, polypropylene or paper based.

[0036] The object is also achieved by a method for producing a water-based barrier adhesive as defined herein, comprising: providing an aqueous solution comprising at least one water-soluble polymer; and mixing the aqueous solution with a polyurethane.

[0037] Providing an aqueous solution may include dissolving a water-soluble polymer in water. The dissolution of the water-soluble polymer in water may be performed at a temperature in the range of 50° C. to 150° C. The water-soluble polymer may be dissolved in water in an amount of 1 wt % to 30 wt % relative to the total amount of the aqueous solution. The method may further include cooling the temperature of the aqueous solution after dissolving one or more water-soluble polymers in water.

[0038] The water-soluble polymer used in the method may be selected from the group consisting of polyvinyl alcohol, poly(ethylene vinyl alcohol), polyvinyl acetate, poly(ethylene vinyl acetate), cellulose acetate, and mixtures thereof. The water-soluble polymer used in the method may have a degree of hydrolysis of 70 to 100% relative to the total number of hydrolyzable groups in the water-soluble polymer. The water-soluble polymer used in the method may have a weight average molecular weight of 500 to 50,000 g / mol, preferably 20,000 to 40,000 g / mol.

[0039] The water-based barrier adhesive may further comprise a water-soluble solvent. Relative to the total weight of the water-based barrier adhesive, the water-based barrier adhesive may comprise 0.1 to 50 wt%, preferably 0.1 to 30 wt%, more preferably 10 to 20 wt% of a water-soluble solvent. The water-soluble solvent may be selected from the group consisting of methanol, ethanol, propanol, butanol, and mixtures thereof.

[0040] In the method of the present invention, mixing the aqueous solution with the polyurethane may include adding the polyurethane to the aqueous solution over a duration of at least 5 minutes.

[0041] Addition of the polyurethane to the aqueous solution may be carried out at a temperature in the range of 25°C to 40°C.

[0042] The weight ratio of the polyurethane to the water-soluble polymer may be 5:1 to 1:30.

[0043] Finally, the object is achieved by the use of a water-based barrier adhesive as a barrier adhesive layer in food packaging.

[0044] Beneficial Effects

[0045] The inventors surprisingly found that water-based barrier adhesives according to the present disclosure can be used as barrier adhesives, particularly in food packaging, and in this regard help improve barrier properties, particularly with respect to oxygen transmission rate (OTR) and water vapor transmission rate (WVTR).

[0046] The present inventors have further discovered that the above-mentioned advantageous barrier properties are combined with good film appearance and adhesive properties.

[0047] Another advantage is that the water-based barrier adhesives of the present invention combine improved barrier properties with recyclability.

[0048] Recently, as a trend towards recyclability, there are attempts to develop monomaterials for packaging (particularly flexible packaging), for example, multilayer films for packaging, having at least about 70% monomaterial (i.e., recycled components), preferably at least 90% monomaterial (i.e., recycled components), depending on the design of the total film thickness and the coating weight or coating thickness of the non-recyclable components. The water-based barrier adhesive of the present invention allows the preparation of laminated films containing >95% monomaterial (i.e., recycled components) with good barrier properties. DETAILED DESCRIPTION

[0049] Material

[0050] The polyurethane dispersion (PUD) has a solid content of 32 to 35 wt%. The polyurethane is composed of aliphatic polyether urethane and aliphatic polyester urethane with a weight average molecular weight of about 40,000 to 90,000 g / mol. The materials used in the following examples are sold under the trade name NeoRez TM Available from DSM Coating Resins and under the trade name LOCTITE TM Purchased from Henkel Company.

[0051] Polyvinyl alcohol (PVA) has a weight average molecular weight of 20,000 to 40,000 g / mol and a degree of hydrolysis of 96. Each material used in the following examples is a product manufactured under the trade name FujiFilm Wako TM From FUJIFILM Wako Pure Chemical Corporation, under the trade name Poval TM and Exeval TM It is available from Kuraray Company, from Mitsubishi Chemical Corporation under the trade name GOHSENOL, and from DENKA Company under the trade name DENKA POVAL.

[0052] Poly(acrylic acid) (PAA) has a viscosity average molecular weight (Mv) of 300,000 to 500,000 Daltons, a Brookfield viscosity of 100 to 3,000 cP, and a glass transition temperature of 100 to 110 degrees C. Each material used in the following examples was purchased from Sigma Aldrich.

[0053] Measurement method

[0054] granularity

[0055] Particle size (= particle diameter) and specific surface area were measured by Zetasizer Nanoseries model S4700 (Malvern Instrument, UK), where the sample was diluted in deionized water at a concentration of about 0.001 to 0.003 wt%, the dispersant refractive index was 1.33 and the particle refractive index was 1.56.

[0056] Viscosity

[0057] The solution viscosity was measured by a Brookfield viscometer at 25°C with needle No. 18, a torque value greater than 90% and a speed of 14-30 rpm.

[0058] Molecular weight

[0059] The number average molecular weight (Mn), weight average molecular weight (Mw) and Z average molecular weight (Mz) were evaluated by gel permeation chromatography (GPC) using a THF system, a flow rate of 1.00 mL / min, an injection value of 100 μL, a detector temperature of 35°C, a column temperature of 35°C, and a sample concentration of 1.999, 4.001, 5.999 mg / mL.

[0060] Oxygen Transmission Rate

[0061] The oxygen transmission rate was measured at 23°C and 0% relative humidity (%RH). 2 / 21MT) oxygen transmission rate (OTR) (cc / m2 / day) was measured according to ASTM D3985.

[0062] Water vapor transmission rate

[0063] The water vapor transmission rate (WVTR) (g / m2 / day) was measured using a water vapor permeation analyzer (Systech Illinois, 7002) according to ASTM F1249 at 38°C and 90% RH.

[0064] Initial adhesiveness of tape

[0065] Initial tack was determined by the tape test according to ASTM F 2296. Briefly, a transparent tape was placed on the coated film. After ensuring good contact between the tape and the coated film, the tape was quickly removed by hand. The removed tape and the coated film were then visually inspected.

[0066] Adhesion strength

[0067] The adhesion strength (N / 15 mm) was measured using a universal testing machine (UTM) at an applied load of 100 N and a peeling speed of 254 mm / min. The sample width was constantly fixed at 15 mm.

[0068] Film appearance

[0069] The film appearance was observed visually and also analyzed under a scanning electron microscope (SEM).

[0070] Preparation of water-based barrier adhesives

[0071] Comparative Example 1

[0072] The PVA solution is prepared by dissolving PVA in water at a temperature of 90 to 95° C. It is then cooled to ambient temperature under ambient atmosphere with a stirring speed of about 300 to 800 rpm for about 1 to 2 hours.

[0073] Comparative Example 2

[0074] The PAA solution was prepared by dissolving PAA in water at a temperature of 90 to 95° C. It was then cooled to ambient temperature under ambient atmosphere with a stirring speed of about 300 to 800 rpm for about 1 to 2 hours.

[0075] Comparative Example 3

[0076] The PVA solutions and PAA solutions prepared in Comparative Examples 1 and 2 were mixed in the partial ratios shown in Table 1.

[0077] Examples 4, 5, 6 and 7

[0078] The PVA solution is prepared by dissolving PVA in water or a water-methanol mixture at a temperature of 90 to 95° C. It is then cooled to ambient temperature under ambient atmosphere with a stirring speed of about 300 to 800 rpm for about 1 to 2 hours.

[0079] PUD was slowly added to PVA for about 10 to 30 min, and then kept stirring continuously for 3 to 5 hours until a homogeneous PUD-PVA solution was obtained.

[0080] The ratio of PVA to PUD is shown in Table 1 as a partial ratio.

[0081] Membrane preparation

[0082] Samples 1a to 7a

[0083] Commercially available biaxially oriented polypropylene (BOPP) was coated at a thickness of about 20 μm with the barrier adhesive prepared as described above at a coating weight of less than 3.0 gsm or a thickness of about 1 to 2 μm using a multifunctional coater (VCML, RK Printcoat Instruments).

[0084] Comparative Samples 1a, 2a, 3a, 4a, 5a, 6a, and 7a were prepared by using Comparative Samples 1, 2, 3, 4, 5, 6, and 7, respectively.

[0085] Samples 5b, 5c and 5d

[0086] Sample 5a was then laminated with a cast polypropylene (cPP) film having a thickness of 40 μm, a linear low density polyethylene (LLDPE) having a thickness of 80 μm, or a BOPP film having a thickness of 20 to 80 μm. Adhesive curing was accomplished by maintaining the laminated film at a temperature of 50°C for at least 24 h.

[0087] As can be seen from Table 1, Samples 4 to 7 show better OTR values ​​than all Comparative Examples 1 to 3. In addition, when the PVA content increases relative to the decrease in PU content, the OTR value tends to increase significantly, as shown in Samples 4 and 5. However, too much increase in PVA content results in a decrease in the initial tack and adhesion strength of the barrier adhesive or coating on the coated film substrate, as shown in Samples 5 and 6. In addition, the adhesive composition and barrier film properties of the semi-aqueous barrier adhesive are shown in Sample 7, which is designed to improve the drying properties of the adhesive solution during the lamination or coating process and the residual carrier solvent on the barrier film, while maintaining the barrier properties, compared to our original water-based barrier adhesive.

[0088]

[0089] *The film references of BOPP (20um) and CPP (40um) have values ​​≥ 2,000cc / m2 / day in OTR and 8 to 11 g / m2 / day in WVTR, **MF is material failure / film (substrate) tear, which means that it can reach maximum adhesion on the coated film, AF is adhesion failure / delamination, which means that the adhesion of the adhesive or coating does not have sufficient adhesion strength on the coated film substrate and it needs to be improved as an adhesion function.

[0090] Table 2: The properties of laminated films with different film structures are shown in Table 2.

[0091]

[0092] ***MF is material damage / film tear, AF is adhesion failure / delamination

[0093] Table 2 shows that laminated film samples 5b, 5c and 5d provide excellent OTR and WVTR values. In addition, these structures include greater than 90% polyolefin, which provides recyclability and makes the material suitable for packaging, especially food packaging.

[0094] The features disclosed in the preceding description and in the dependent claims may be essential both individually and in any combination for the implementation of the aspects of the disclosure set out in the independent claims (in their various forms).

Claims

1. A water-based barrier adhesive comprising: Polyurethane; at least one water-soluble polymer, wherein the water-soluble polymer comprises at least one hydroxyl group; and water; in, The polyurethanes include polyether urethanes and aliphatic polyester urethanes; in, (A) the polyurethane and the at least one water-soluble polymer are contained in the water-based barrier adhesive in a weight ratio of 1:1 to 1:5; or (B) The polyurethane and the at least one water-soluble polymer are contained in the water-based barrier adhesive in a weight ratio of 5:1 to 1:30, and the water-based barrier adhesive further contains a water-soluble solvent.

2. The water-based barrier adhesive according to claim 1, wherein The water-based barrier adhesive includes the polyurethane in an amount of 1 to 30 wt % relative to the total weight of the water-based barrier adhesive.

3. The water-based barrier adhesive according to claim 1, wherein The water-based barrier adhesive comprises the at least one water-soluble polymer in an amount of 5 to 60 wt % relative to the total weight of the water-based barrier adhesive.

4. The water-based barrier adhesive of claim 1, further comprising at least one additive. 5 . The water-based barrier adhesive according to claim 4 , wherein the amount of the additive is 0.1 to 10 wt % relative to the total weight of the water-based barrier adhesive.

6. The water-based barrier adhesive of claim 1, wherein: The water soluble polymer is selected from the group consisting of polyvinyl alcohol, poly(ethylene vinyl alcohol), polyvinyl acetate, poly(ethylene vinyl acetate), cellulose acetate, and mixtures thereof.

7. A barrier film comprising a substrate and a barrier adhesive layer coated on at least a surface of the substrate, wherein the barrier adhesive layer comprises the water-based barrier adhesive according to any one of claims 1 to 6.

8. The barrier film according to claim 7, wherein: The barrier adhesive layer coated on the substrate has a thickness of 0.1 to 10 μm.

9. The barrier film according to claim 7, wherein: The water-based barrier adhesive has a concentration of 0.1 to 5 g / m 2 An amount of is applied on the surface.

10. The barrier film of claim 8, further comprising a laminate layer adjacent to the barrier adhesive layer, wherein the barrier adhesive layer is disposed between the laminate layer and the substrate.

11. The barrier film according to claim 10, wherein: The substrate and / or the laminate layer comprises polyethylene, polypropylene or paper.

12. A method of producing a water-based barrier adhesive according to any one of claims 1 to 6, the method comprising: - providing an aqueous solution comprising said at least one water-soluble polymer; as well as - Mixing the aqueous solution with the polyurethane.

13. Use of the water-based barrier adhesive according to claim 1 as a barrier adhesive layer in packaging.

Citation Information

Patent Citations

  • Aqueous coating agent and gas barrier film

    US20160040035A1

  • Laminate film structures having barrier adhesive layer

    WO2019060026A1

  • Preparation method of polyvinyl alcohol modified waterborne polyurethane

    CN103589135A

  • Aqueous coating agent and gas barrier film

    CN105378008A

  • PVA laminated multi layer film with the property of high gas barrier and water resistance and its manufacturing method

    KR1020110075617A